Consumidor, perdoa-me por me traíres : o consumo de narrativas sobre infidelidade na obra de Nelson Rodrigues e na publicidade - Scatigno, Danilo Costa (2017)
Between desire and guilt is the human being, hostage of a search for ideal love that does not there is, therefore, the dramatic substance that inspires the writer Nelson Rodrigues. And not only to the author, also to the brands. How are the advertising narratives that of infidelity? We will approach the nuances of the discursive formation of these narratives with the to understand their correlations with communication and consumption. For this, they will help in this discussion authors such as Eni Orlandi, João Anzanello Carrascoza, Maria Aparecida Baccega and Sábato Magaldi. As a research methodology, we will use the concept of the re-contextualization of Gianfranco Bettetini, in which a text is moved from the original domain to another, so that there is a discursive interaction. The theoretical assumptions of French discourse will help us to demonstrate in what discursive contexts Nelson Rodrigues's short stories and the publicity films study.